Farmers’ responses to farmer field schools (FFS) on integrated crop management: a case study in East Lombok, Indonesia - Abdullatip, Abdullatip; Anwar, Muhammad; Sarlan, Muhammad; Prasetyowati, Rini Endang (Journal of Agricultural Socio-Economics (JASE), 2025)
The government is trying to maintain domestic food self-sufficiency by promoting field school programs to increase institutional empowerment of farmer groups to adopt technology in order to maintain land productivity and farming. The purpose of this study was to analyze the factors that influence farmers' responses to Farmer Field Schools (FFS)-Integrated Crop Management in the Batu Keliang Farmer Group. The research location was deliberately selected in the Batu Keliang Farmer Group, Pejaring Village, Sakra Barat District, East Lombok Regency because it participated in the SLPTT program. Respondents used a census technique involving all members of the population as respondents, totaling 25 people. Data were analyzed using a Likert scale and multiple linear functions. The conclusion of the study is that farmers' responses to the SLPTT rice field program in the Batu Farmer Group were simultaneously 65.9% influenced by all independent variables of age (X1), education (X2), land area (X3), rice farming experience (X4), number of family dependents (X5), and active participation in the program (X6). While the partial influence has two significant independent variables, namely education (X2) and number of family members (X5).